A Semiotic Analysis of the Verbal and Non-Verbal Slogans Used in the Day of Ashura - Prof. Dr. Hashim A. M. Alhusseini; Assis.Lect. Rasha Hilal Kareem; Dr. Adnan Z. Mkhelif; Assis.Lect. Iltifat Aliwi Mohamme (Journal of College of Education, 2024)
Slogans serve multifaceted purposes. They elucidate intricate concepts, articulate group philosophies and objectives, foster identification, spark violent conflicts, and anticipate future expectations. This study delves into the examination of the slogans articulated by Imam Al-Hussein (peace be upon him) or his adherents during Ashura revolution in response to the deviations in Yazid’s rule. The primary objective is to unravel the meanings embedded in the visual signs, encompassing both denotation and connotation, inherent in these slogans. Employing Barthes’s (1968) semiotic theory, the researchers scrutinize six selected images, each featuring impactful slogans sourced from various websites. The analysis reveals that these images encompass a fusion of verbal and non-verbal signs. Furthermore, the study finds that slogans not only have denotative meanings, but are also rich in various connotations. The inclusion of colour in conjunction with the slogans in the images is a deliberate strategy to capture the reader’s attention and evoke psychological responses.